Preferences, government investment, and disbursement sudden stops - Dacuycuy, Lawrence B. (2016)
Motivated by a recent fiscal episode in the Philippines, during which a major policy initiative was launched to counter poor fiscal spending performance, this note explores the properties of a neoclassical model when a structure that introduces shocks to authorized spending alongside unanticipated government investment shocks is integrated into the model. With the possibility of disbursement flow stops as a backdrop, it investigates the role of preference structures using the model of Leeper, Walker, and Yang [2010], augmented with some useful features from the fiscal-centric dynamic stochastic general equilibrium (dsge) model of Coenen, Straub, and Trabandt [2013]. We argue that the two shocks are orthogonal, with the former deemed more related to persistent shocks arising from budgetary reforms given trends in disbursement rates. Unlike government consumption, government investments add up to a country’s capital stock, which can predictably improve the efficacy of future government investments and consumption. Results indicate that shocks to government investment have systemic effects on output, labor supply, government investment, and government consumption. More importantly, preference structures do matter in evaluating the impact of various shocks.
Keywords: Fiscal policy; Public spending